2008
DOI: 10.1111/j.1365-2109.2008.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish farming on the water column nutrient concentration in a semi-enclosed gulf of the Eastern Mediterranean

Abstract: The spatial and seasonal impact of ¢sh farming on the water column of two ¢sh farms in the Eastern Mediterranean was investigated, between July 2004 and April 2005. In the area of each ¢sh farm, three stations were sampled. One was located at the centre of the ¢sh farm, the other at a distance of 50 m from the centre and the last one at a distance of 300 m from the ¢sh farm centre. At each sampling station, water samples were collected at the surface, at 5 m and at every further 10-m depth from the surface to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…Nitrate is found in well-oxygenated waters and its variability is due to biological activity (Neofitou and Relative abundance (%) of zooplankton groups in the fish pond at the different samples sites (P 1 -P 6 ) during the studied period. Klaoudatos, 2008). The above was confirmed in current research since high nitrate concentrations, when compared with other nutrients (TP, orthophosphate and ammonia), may be associated with dissolved oxygen above 4 mg.L -1 and the continuous water flow which is heightened during the summer when heavy rains occur.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Nitrate is found in well-oxygenated waters and its variability is due to biological activity (Neofitou and Relative abundance (%) of zooplankton groups in the fish pond at the different samples sites (P 1 -P 6 ) during the studied period. Klaoudatos, 2008). The above was confirmed in current research since high nitrate concentrations, when compared with other nutrients (TP, orthophosphate and ammonia), may be associated with dissolved oxygen above 4 mg.L -1 and the continuous water flow which is heightened during the summer when heavy rains occur.…”
Section: Discussionsupporting
confidence: 74%
“…The greatest abundances of Cyanobacteria were observed in the site P 1 where orthophosphate concentration was at its lowest Cyanobacteria abundance might have been influenced by a favourable N:P ratio. Further shallow systems are characterised by phosphate limitation because the biologically available phosphorus amount is small when the quantity required for algal growth is take into consideration (Neofitou and Klaoudatos, 2008). Orthophosphate concentrations in the current study were lower than 50 mg.L -1 , except at the P 6 (September) site.…”
Section: Sc F Sc F Sc F Sc F Sc F Sc F Cladoceramentioning
confidence: 91%
See 1 more Smart Citation
“…The impact of fin fish aquaculture has been widely reported in the benthos, where common degradation patterns have been observed (Kalantzi and Karakassis, 2006), since the seabed is able to record possible detrimental effects to the environment over long periods of time (Danovaro, 2003). In the water column however, the effects are less obvious (Neofitou and Klaoudatos, 2008), and any differences in the measured parameters are usually more influenced by seasonality than aquaculture wastes (Pitta et al, 1998;Yucel-Gier et al, 2008). Indeed, water column parameters are often not correlated with the extent of benthic impact.…”
Section: Eliminado: Ismentioning
confidence: 99%
“…Some studies have analysed metals and pigments found in sediments as well as bacteria and multiple stable isotopes as indicators of environmental impact (Mazzola et al 2000;Kaymakci et al 2010). Others have focused on the environmental impact of aquaculture activities on nutrients and plankton (Neofitou and Klaoudatos 2008); on nutrients and benthic community structure (Mazzola et al 2000;Yucel-Gier et al 2007); and on the geochemistry of sediments and benthic organisms Mazzola et al 2000).…”
Section: Introductionmentioning
confidence: 99%